DESA DAN LEGITIMASI KEBERDAYAAN SOSIAL; TELAAH IMPLEMENTASI KEBIJAKAN UU No. 6/2014 TENTANG DESA DI KABUPATEN MALANG - Sri Hartini Jatmikowati; Titot Edy Suroso (Universitas Merdeka Malang, 2016)
Removable policy on the village always occur within the period of the ruling regime. As a result, the identity of the villagers 'eroded' by age. The birth of a new policy on the village in 2014 is a new spirit in the effort and equitable development as well as efforts for the welfare of rural communities by involving all social potential which is owned by the village. The study has been completed, is intended to explain the issue of How the Governing Village Welfare Society in Efforts to Achieve? By using qualitative methods eksplanatif, this study found several things to encourage social empowerment of rural communities such as formal institutions and informal institutions. Formal institutional legitimate by the government is a great potential in achieving sustainable development mission for the government. Meanwhile, informal institutions that are owned by the villages despite the growing body and not significantly, yet its existence can be used as a means of unifying as well as social control in the development process.DOI: https://doi.org/10.26905/pjiap.v1i2.507